PENGARUH BUDAYA SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA (SURVEI DI SMK JAKARTA PUSAT 1) - Kurnia Illahi; Nadiah; Kunaenih; Zahra Eka Sawitri; Nur Alifiah Zanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School culture plays an essential role in shaping students' character through the internalization of values, norms, habits, and positive behaviors within the school environment. However, various disciplinary violations and inappropriate behaviors among students indicate that the implementation of school culture has not yet optimally supported character development. This study aimed to determine the effect of school culture on students' character formation, measure the magnitude of its contribution, and provide an overview of strengthening school culture in supporting character education. The study employed a quantitative approach using a correlational survey method. The population consisted of students at SMK Jakarta Pusat 1, with 34 respondents selected through simple random sampling. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using the Pearson Product Moment correlation technique. The findings revealed a positive and significant effect of school culture on students' character formation, with a correlation coefficient (r) of 0.554. The obtained correlation coefficient exceeded the critical value of the r-table at both the 5% significance level (0.344) and the 1% significance level (0.442), indicating that the alternative hypothesis was accepted. These findings suggest that a positive and consistently implemented school culture contributes to the development of students' character, particularly in fostering discipline, responsibility, and positive attitudes in the school environment.